2016
DOI: 10.1242/jeb.137315
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic underpinnings of dehydration stress in the American dog tick revealed through RNA-Seq and metabolomics

Abstract: Ticks are obligate blood feeders but spend the majority of their lifetime off-host where they must contend with a multitude of environmental stresses. Survival under desiccating conditions is a determinant for habitats where ticks can become established, and water-balance characteristics of ticks have been extensively studied. However, little is known about the underlying aspects associated with dehydration stress in ticks. In this study, we examined the response of male American dog ticks, Dermacentor variabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 77 publications
1
58
0
Order By: Relevance
“…Although protein usage in starved ticks has received little attention, it seems to be an important source of energy, particularly during extended starvation and environmental stress (Jaworski et al., ; Rosendale, Romick‐Rosendale, Watanabe, Dunlevy, & Benoit, ; Rosendale et al., ). In our ticks, the utilization of protein stores was facilitated by changes in metabolic pathways related to protein degradation during starvation, including an upregulation of proteolysis‐related genes and a downregulation of peptidase inhibitors (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Although protein usage in starved ticks has received little attention, it seems to be an important source of energy, particularly during extended starvation and environmental stress (Jaworski et al., ; Rosendale, Romick‐Rosendale, Watanabe, Dunlevy, & Benoit, ; Rosendale et al., ). In our ticks, the utilization of protein stores was facilitated by changes in metabolic pathways related to protein degradation during starvation, including an upregulation of proteolysis‐related genes and a downregulation of peptidase inhibitors (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…GABA is considered to be effective immunomoldulatory molecule and plays an important role in autoimmune diseases such as type 1 diabetes and rheumatoid arthritis57. A recent study of mechanistic aspects of dehydration stress in the American dog tick showed accumulation of GABA in ticks, although its specific role is unknown58. Another work of relating stress with GABA level was reported in a metabolomic study of soybean leaves with iron deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…via CRISPR/Cas9 technology (Gratz et al, 2013) or RNA interference (RNAi; Scott et al, 2013)] or increasing cryoprotectant abundance [e.g. Generate knockout mutants Gratz et al (2013) by feeding (Koštál et al, 2016) or injection Rosendale et al, 2016)]. If cryoprotectant manipulations reduce or enhance freeze tolerance (loss-and gain-of-function, respectively), we can conclude that they contribute to the mechanisms underlying freeze tolerance.…”
Section: (2) Models and Experimental Manipulations For Understanding mentioning
confidence: 99%